(untitled) (Global Journal of Management and Business Research, 2023)
As a result of a rapid increase in inventory management and the time required to manage inventory management, many organizations have resulted to the tracking of inventory. Due to this, there should be some means of accurately tracking inventory. Due to this, there should be some means of accurately tracking inventory in order to ease the management of inventory. Some of the most useful methods of tracking inventory are barcodes where every item carries a label that gives information on the items, stock books and the Kanban system. It is against this background that the main endeavour of this project is to investigate if inconsistent tracking has an impact of inventory management with specific objective being to find out the impact of documentation on inventory management. From these objectives the following questions were asked; what impact does inconsistent tracking have on inventory management. The theories adapted to back this work were; The Just In Time theory by Taiichi Ohno (1984), The Wilson’s Model for Inventory Management by R.H Wilson (1934) and the Theory of Constraints by Dr Eliyah Goldrath (1984). The methods of data collection included primary and secondary sources. Conclusions were drawn from the data collected and recommendations were made such as making proper use of the available tracking software.